2016
DOI: 10.1002/2016gl070969
|View full text |Cite
|
Sign up to set email alerts
|

Meltwater pathways from marine terminating glaciers of the Greenland ice sheet

Abstract: The Greenland ice sheet (GrIS) stores the largest amount of freshwater in the Northern Hemisphere and has been recently losing mass at an increasing rate. An eddy‐permitting ocean general circulation model is forced with realistic estimates of freshwater flux from the GrIS. Two approaches are used to track the meltwater and its trajectory in the ocean. We show that freshwater from western and eastern GrIS have markedly different fates, on a decadal time scale. Freshwater from west Greenland predominantly accum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
76
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 77 publications
(83 citation statements)
references
References 53 publications
7
76
0
Order By: Relevance
“…Several regions where freshwater deviates into the interior have been identified downstream of our array in observations: the tip of CF (Holliday et al, ) and the unstable West Greenland Current (Bracco et al, ; Myers et al, ; Rykova et al, ; Schmidt & Send, ). Furthermore, several recent modeling studies have found that freshwater originating east of Greenland is more likely to enter the Labrador Sea than freshwater originating west of Greenland (Gillard et al, ; Luo et al, ; Marson et al, ; Tesdal et al, ; Wang et al, ). In particular, water over the slope east of Greenland is more likely to enter the Labrador Sea than water originating on the shelf (Schulze Chretien & Frajka‐Williams, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several regions where freshwater deviates into the interior have been identified downstream of our array in observations: the tip of CF (Holliday et al, ) and the unstable West Greenland Current (Bracco et al, ; Myers et al, ; Rykova et al, ; Schmidt & Send, ). Furthermore, several recent modeling studies have found that freshwater originating east of Greenland is more likely to enter the Labrador Sea than freshwater originating west of Greenland (Gillard et al, ; Luo et al, ; Marson et al, ; Tesdal et al, ; Wang et al, ). In particular, water over the slope east of Greenland is more likely to enter the Labrador Sea than water originating on the shelf (Schulze Chretien & Frajka‐Williams, ).…”
Section: Discussionmentioning
confidence: 99%
“…Freshwater is a key player in the formation of globally significant water masses in the subpolar gyre (Manabe & Stouffer, 1995). In particular, the freshwater flowing east of Greenland, which includes Arctic freshwater and sea ice, as well as Greenland melt and icebergs, has been shown to be the primary source of freshwater for the subpolar gyre interior in recent modeling studies (Gillard et al, 2016;Luo et al, 2016;Marson et al, 2018;Schulze Chretien & Frajka-Williams, 2018;Tesdal et al, 2018;Wang et al, 2018). Freshwater export from the Arctic and Greenland is expected to increase (Alley et al, 2005;Wang & Overland, 2009), with potential consequences for the formation of intermediate North Atlantic Deep Waters and global climate.…”
Section: Introductionmentioning
confidence: 99%
“…The strength of the Atlantic Meridional Overturning Circulation (AMOC) is of concern when considering the increasing freshwater flux from the Greenland Ice Sheet and potential consequences to global ocean circulation and energy transfers (Bamber et al, 2012;Böning et al, 2016;Gillard et al, 2016;Yang et al, 2016). In their modeling studies, Gillard et al (2016), Marson et al (2018), and Wagner and Eisenman (2017) note that direct meltwater input from the Greenland Ice Sheet or via iceberg deterioration could affect deep-water convection in the North Atlantic and potentially lead to a slowdown of the AMOC. However, a sustained freshwater flux anomaly of at least 7 mSv in the North Atlantic is thought to be necessary to substantially slowdown the AMOC (Brunnabrend et al, 2015;Yang et al, 2016).…”
Section: Meltwater Dispersalmentioning
confidence: 99%
“…Many of the earlier studies have used an idealized FWF, typically averaged zonally and sometimes with unrealistically large flux anomalies (Gerdes et al, 2006;Hu et al, 2009;Jungclaus et al, 2006). More recently, experiments have used an observational and model-based estimate of FWF from the GrIS to investigate its potential role on the hydrography of the SNA and influence on the Atlantic Meridional Overturning Circulation (AMOC) (Boning et al, 2016;Dukhovskoy et al, 2016;Gillard et al, 2016;Marsh et al, 2010;Yang et al, 2016). From these analyses, it has been suggested, for example, that changes to deep Labrador Sea Water are linked to enhanced FWF from the GrIS (Yang et al, 2016) and that, if the FWF trend continues, it could play an important role in modulating the strength of the AMOC (Boning et al, 2016).…”
Section: Introductionmentioning
confidence: 99%